Development of a simulation model for swimming with diving fins - Nakashima, M.; Tanno, Y.; Fujimoto, T.; Masutani, Y. (Proceedings, 2018)
The simulation model to assess the performance of diving fin was developed by extending the swimming human simulation model SWUM. A diving fin was modeled as a series of five rigid plates and connected to the human model by springs and dampers. These plates were connected to each other by virtual springs and dampers, and fin`s bending property was represented by springs and dampers as well. An actual diver`s swimming motion with fins was acquired by a motion capture experiment. In order to determine the bending property of the fin, two bending tests on land were conducted. In addition, an experiment was conducted in order to determine the fluid force coefficients in the fluid force model for the fin. Finally, using all measured and identified information, a simulation, in which the experimental situation was reproduced, was carried out. It was confirmed that the diver in the simulation propelled forward in the water successfully.